The Role of Local Government in Accelerating Sustainable Economic Development in Sungai Penuh City - Silvia Rahayu; Erni Febrina Harahap; Dorris Yadewani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the role of local government in promoting sustainable economic development in Sungai Penuh City. The research employs a descriptive qualitative method with a literature study approach. The findings reveal that the local government plays a central role as: (1) a catalyst for the transition toward a green economy, (2) an integrator of diverse local interests and potentials, (3) a guardian of environmental sustainability and local wisdom, and (4) an innovator in formulating contextually appropriate solutions. By leveraging its strategic location within a conservation area and the local wisdom of its communities, Sungai Penuh has the potential to become a model for ecosystem-based sustainable urban development that preserves the Kerinci Seblat National Park (TNKS) while fostering inclusive prosperity for its citizens.